The Impact of a six week exergaming curriculum on balance with grade three school children using the Wii FIT+ - Sheehan, D. P.; Katz, L. (International Journal of Computer Science in Sport, 2012)
The development of fundamental movement skills (FMS) is at the heart of promoting physical literacy in children. The competence to perform basic motor tasks coupled with the confidence to try new activities will encourage children to embrace a positive attitude about being active for life. Balance is one FMS that can be specifically targeted for improvement and assessment. This paper explores the school-based application of exergaming technology as it relates to balance. Third grade students in this study improved their postural stability significantly over a 6-week period compared to a control group. The improvements in postural stability were also evident in a parallel intervention of children receiving more traditional training in agility, balance and coordination (gymnastics and dance). Gender did not have an effect on the changes in postural stability for either group; however, postural stability in the girls was better than the boys in all tests. Based on the results of this study, it is apparent that for the purpose of improving balance in elementary school children, the use of exergaming is emerging as a practical option available to physical educators. Specifically, the Wii Fit+™ has promising potential as an inexpensive and enjoyable tool for the development of balance.